Mobility and fluorescence of barium ions in xenon gas for the EXO experiment - Benitez Medina, Julio Cesar, author; Fairbank, William, advisor; Berger, Bruce, committee member; Lundeen, Stephen, committee member; Menoni, Carmen, committee member (Colorado State University. Libraries, 2014)
The Enriched Xenon Observatory (EXO) is an experiment which aims to observe the neutrinoless double beta decay of 136Xe. The measurement of this decay would give information about the absolute neutrino mass and whether or not the neutrino is its own antiparticle. Since this is a very rare decay, the ability to reject background events by detecting the barium ion daughter from the double beta decay would be a major advantage. EXO is currently operating a detector with 200 kg of enriched liquid xenon, and there are plans to build a ton scale xenon detector. Measurements of the purity of liquid xenon in our liquid xenon test cell are reported. These results are relevant to the research on detection of single barium ions by our research group at Colorado State University. Details of the operation of the purity monitor are described. The effects of using a purifier, recirculation and laser ablation on the purity of liquid xenon are discussed. Mobility measurements of barium in xenon gas are reported for the first time. The variation of mobility with xenon gas pressure suggests that a significant fraction of molecular ions are formed when barium ions interact with xenon gas at high pressures. The measured mobility of Ba+ in Xe gas at different pressures is compared with the predicted theoretical value, and deviations are explained by a model that describes the fraction of molecular ions in Xe gas as a function of pressure. The results are useful for the analysis of experiments of fluorescence of Ba+ in xenon gas. It is also important to know the mobility of the ions in order to calculate the time they interact with an excitation laser in fluorescence experiments and in proposed 136Ba+ daughter detection schemes. This thesis presents results of detection of laser induced fluorescence of Ba+ ions in Xe gas. Measurements of the pressure broadening of the excitation spectra of Ba+ in xenon gas are presented. Nonradiative decays due to gas collisions and optical pumping affect the number of fluorescence counts detected. A model that treats the barium ion as a three level system is used to predict the total number of fluorescence counts and correct for optical pumping. A pressure broadening coefficient for Ba+ in xenon gas is extracted and limits for p-d and d-s nonradiative decay rates are extracted. Although fluorescence is reduced significantly at 5-10 atm xenon pressure, the measurements in this thesis indicate that it is still feasible to detect 136Ba+ ions directly in high pressure xenon gas, e.g. in a double beta decay detector.
Keywords: barium; exo; fluorescence; mobility; purity; xenon